Lung cancer screening CT acquisition protocols for three generations of CT systems conforming to German legislation - Sawall, Stefan; Maier, Joscha; Ziener, Christian H.; Schlemmer, Heinz-Peter; Do, Thuy; Kauczor, Hans-Ulrich; Schönberg, Stefan; Froelich, Matthias F.; Kachelrieß, Marc (Physica medica, 2025)
Objective - Develop a computed tomography (CT) acquisition protocol for lung cancer screening compliant with German legislation across three CT system generations, addressing standardization of image quality and radiation dose amid technical variability. - Materials and methods - Three CT systems, a first-generation dual-source energy-integrating (EID) CT (Somatom Flash), a second-generation dual-source EID CT (Somatom Force), and a photon-counting CT (Naeotom Alpha), were evaluated. An anthropomorphic thorax phantom with fat rings was used to simulate small, medium, and large patients and included lesions with 150 HU contrast. Image quality was quantified via contrast-to-noise ratio (CNR) at multiple dose levels. Focus was placed on the system-specific adaptation of acquisition and reconstruction parameters, reflecting the challenges faced in harmonizing imaging protocols across diverse hardware generations. - Results - At matched CTDI, CNR varied markedly, with newer systems performing best. Thicker slices improved CNR. To reach the defined target of a CNR of 2.2 on 3.0 mm slices, the required CTDI were, in the small phantom, Flash and Force about 0.37 mGy and Alpha 0.26-0.19 mGy. In the medium phantom, Flash 1.30 mGy, Force about 0.96 mGy, and Alpha 0.46-0.24 mGy. In the large phantom, Flash 3.34 mGy, Force 5.15 mGy, and Alpha 2.08-0.69 mGy. Required dose increased with phantom size and differed by system generation, underscoring the clinical difficulty of “one-size-fits-all” dose specifications. - Conclusions - Uniform protocol implementation across CT platforms is challenged by hardware and reconstruction disparities. Patient-size-adapted and system-specific protocols are essential to balance diagnostic performance and radiation safety for future lung cancer screening programs.